2021
DOI: 10.1039/d1nr03273a
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism and atomic structure of group-IIA compound-promoted CVD-synthesized monolayer transition metal dichalcogenides

Abstract: Developing promoters that can boost the growth quality, efficiency, and robustness of two-dimensional (2D) transition metal dichalcogenides is significant for their industrial applications. Herein, a new group (group IIA) of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The CVD synthesis of monolayer MoS 2 was reported in the previous work. [ 67 ] Prior to the encapsulation of 1T’‐MoTe 2 , the CVD‐grown monolayer MoS 2 was transferred onto the flexible polydimethylsiloxane (PDMS, Aladdin) by a PMMA‐etching‐free method. As the surface energy was different between the hydrophobic MoS 2 and hydrophilic NaCl‐modified SiO 2 , water spontaneously penetrated into the MoS 2 /substrate interface to delaminate MoS 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The CVD synthesis of monolayer MoS 2 was reported in the previous work. [ 67 ] Prior to the encapsulation of 1T’‐MoTe 2 , the CVD‐grown monolayer MoS 2 was transferred onto the flexible polydimethylsiloxane (PDMS, Aladdin) by a PMMA‐etching‐free method. As the surface energy was different between the hydrophobic MoS 2 and hydrophilic NaCl‐modified SiO 2 , water spontaneously penetrated into the MoS 2 /substrate interface to delaminate MoS 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This result was verified by considering a previously reported study. 40 Second, the cationic surfactant hexamethonium (HM) bromide was used for dispersing the Co-MoS 2 nanosheets and preventing them from stacking in the [002] direction, resulting in the formation of single- or few-layer Co-MoS 2 protected by organic buffer layers. As the previous studies suggested, the expanded interlayer spacing of MoS 2 can be beneficial for the formation of 1T-MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…39 It is speculated that the appearance of Co-doped 1T-MoS 2 may originate from the large interlayer spacing with small size regulated by the spatially restricted domain and the electron-modulating effect of Co doping. 40,41 Thus, the truncated triangular morphology, few-layer stacking, and reduced lateral size observed in 1T-Co-MoS 2 @HMCS could be attributed to the synergistically confined growth effect from the atomic level to the mesoscopic scale, which benefits from the hierarchical structural (Co 2 Mo 10 )(HM) 3 @HMCS precursor and in situ vapour-phase sulfurization approach.…”
Section: Preparation and Characterization Of 1t-co-mos 2 @Hmcsmentioning
confidence: 99%
“…Techniques for the fabrication of Er-doped TMDs include chemical vapor deposition (CVD), sputtering, and pulse laser deposition . Among them, the CVD method offers the advantage of large-area and high-quality 2D TMDs. , The introduction and dosage of dopants are the key factors that influence the growth of chemically produced films. , However, how Ln-doping affects the growth and optical characteristics of 2D TMDs is still under investigation. Meanwhile, previous studies have demonstrated that Er 3+ doping can significantly enhance the photoresponse of WS 2 films in the visible region. , Given the significance of the NIR band for optical communication, it will be significant to systematically investigate the effects of Er 3+ on the NIR photoresponse of 2D WS 2 .…”
Section: Introductionmentioning
confidence: 99%